Embedding Ethical Constraints into End-to-End AI Pipelines (AI Governance and Society Journal p-ISSN 3117-6097 and e-ISSN 3117-6100, 2024)
End-to-end artificial intelligence (AI) pipelines -- spanning data ingestion, feature engineering, model training, serving, and monitoring -- introduce multiple stages at which ethical violations may emerge, propagate, or amplify. Existing approaches to AI ethics largely address individual pipeline stages in isolation, leaving cross-stage ethical constraint propagation and inter-stage dependency management underexplored. This paper proposes the Ethical Constraint Propagation (ECP) framework, a principled approach to embedding fairness, transparency, privacy, and accountability constraints across all stages of end-to-end AI pipelines through explicit constraint declaration, automated propagation, and stage-level verification gates. The ECP framework is evaluated on n = 20 production AI pipelines drawn from four industry sectors -- healthcare, finance, retail recommendation, and smart infrastructure -- through a combination of static pipeline audit and six-month longitudinal monitoring. Pipelines adopting the full ECP framework exhibited a 43.8% reduction in cross-stage ethical violations (SD = 5.1%) and a 31.4% improvement in end-to-end fairness consistency (SD = 4.6%) relative to unmodified baselines. Privacy constraint leakage -- defined as privacy guarantees established at the data ingestion stage failing to propagate to downstream serving components -- was eliminated in all ECP-compliant pipelines. The study contributes the ECP framework specification, a constraint propagation graph formalism, and an empirical benchmark dataset for ethical AI pipeline evaluation.